Study of antihyperglycaemic properties of selected Malaysian antidiabetic plants in cultured 3T3-L1 cells - Azahari, Nuraniza; Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher; Ichwan, Solachuddin Jauhari Arief (2010)
Diabetes Mellitus is a metabolic disease occuring worldwide caused by defects in insulin secretion, insulin action, or most commonly both. Diabetes mellitus is probably the fastest growing metabolic disease in the world and as knowledge of the heterogeneous nature of the disease increases so does the need for more challenging and appropriate therapies. The aim of the research is to evaluate the antidiabetic properties of selected antidiabetic plants used in the treatment of diabetes mellitus. The selection of plants was based on traditional reputation of usefulness in treating diabetes. Water extracts of Syzgium Polyanthum, Peronema canescens, Orthosiphon Stamineus, Lagerostroemia Speciosa, Momordica Charantia, Tinospara Crispa, Archidendrau Jiringa, Cinnamomum Zeylanicum, and Andrographis Paniculata were selected. Insulin was used as a positive control. The plants were studied on the bioactive peptides (adipokines) using an in-vitro model. 3T3-L1 adipocyte cell line is selected for this study because it plays an important role in lipid storage and glucose homeostasis. The first test is to know the ability of the plants to induce preadipocyte to adipocyte cell by using the mixture of dexamethasone, 1-isobutyl-3-methylxantine and the plant extracts. Then, continue with the MTT assay to study the toxicity level in order to get appropriate dose of the extracts. After that, protein analysis is conduct to demonstrate the plant activity that mimics insulin action. Adipogenesis, adipolysis, adiponectin and leptin protein were analyzed to assess the effect of the extract on lipid synthesis and degradation in the cultured 3T3-L1 cells by using ELISA kit. The result confirms that a preadipocyte cell was differentiated to adipocyte. Preliminary result shows that A. Paniculata and L. Speciosa extracts have strong activity in inducing lipid formation.